Aortopathy in a Mouse Model of Marfan Syndrome Is Not Mediated by Altered Transforming Growth Factor β Signaling. Issue 1 (January 2017) - Wei, Hao; Hu, Jie Hong; Angelov, Stoyan N.; Fox, Kate; Yan, James; Enstrom, Rachel; Smith, Alexandra; Dichek, David A.
Abstract : Background: Marfan syndrome (MFS) is caused by mutations in the gene encoding fibrillin‐1 ( FBN1 ); however, the mechanisms through which fibrillin‐1 deficiency causes MFS‐associated aortopathy are uncertain. Recently, attention was focused on the hypothesis that MFS‐associated aortopathy is caused by increased transforming growth factor‐β (TGF‐β) signaling in aortic medial smooth muscle cells (SMC). However, there are many reasons to doubt that TGF‐β signaling drives MFS‐associated aortopathy. We used a mouse model to test whether SMC TGF‐β signaling is perturbed by a fibrillin‐1 variant that causes MFS and whether blockade of SMC TGF‐β signaling prevents MFS‐associated aortopathy. Methods and Results: MFS mice ( Fbn1 C1039G/+ genotype) were genetically modified to allow postnatal SMC‐specific deletion of the type II TGF‐β receptor (TBRII; essential for physiologic TGF‐β signaling). In young MFS mice with and without superimposed deletion of SMC‐TBRII, we measured aortic dimensions, histopathology, activation of aortic SMC TGF‐β signaling pathways, and changes in aortic SMC gene expression. Young Fbn1 C1039G/+ mice had ascending aortic dilation and significant disruption of aortic medial architecture. Both aortic dilation and disrupted medial architecture were exacerbated by superimposed deletion of TBRII. TGF‐β signaling was unaltered in aortic SMC of young MFS mice; however, SMC‐specific deletion of TBRII in Fbn1 C1039G/+ mice significantly decreased activation of SMC TGF‐β signaling pathways. Conclusions: In young Fbn1 C1039G/+ mice, aortopathy develops in the absence of detectable alterations in SMC TGF‐β signaling. Loss of physiologic SMC TGF‐β signaling exacerbates MFS‐associated aortopathy. Our data support a protective role for SMC TGF‐β signaling during early development of MFS‐associated aortopathy.